Predictive Factors of Diabetes Mellitus Self-Management (DMSM) Practice: A Systematic Review and Meta-Analysis - Pamungkas, Rian Adi; Usman, Andi Mayasari; Chamroonsawasdi, Kanittha; Sari, Widia (Jurnal Keperawatan Soedirman, 2024)
The diabetes mellitus self-management (DMSM) is integral to controlling blood glucose and preventing diabetes complications. There were still gaps in the analysis controversy of the outcome that need to be explored by systematic review and meta-analysis. The review aimed to synthesize the predictive factors associated with practice DMSM practice among Type 2 Diabetes Mellitus (T2DM). This study applied the systematic and meta-analysis method. Three databases, Scopus, PubMed, and Medline, were included in this study to obtain the relevant articles. Keywords used were “self-management”; “diabetes mellitus”; self-care; factors associated with self-management". Comprehensive Meta-Analysis (CMA) was used to analyze and interpret the effect size of the review study. The results showed that 15 predictive factors were associated with DMSM practice, including age, sex, education level, illness duration, and financial barriers. Diabetes knowledge, insulin in treatment, belief of treatment, social support, occupational, personality, diabetes-specific emotional distress, perception of the disease, quality interaction with healthcare providers, and self-efficacy were considered predictive factors. The findings suggested that a wide range of personal and environmental factors were the most influential factors associated with the implementation of DMSM in health care services. Therefore, it is vital to construct theory-based strategies to improve DMSM practice among diabetes population.